Conical, Stair-Shapedand Cylindrical Dielectric Resonator Antenna for Early Breast Cancer Detection Application - Fokoa, Gwladys Laure Makiela; Uyguroglu, Rasime (IEEE, 2019)
This study is about the design of Dielectric Resonator Antennas (DRAs) in the X-band (8 GHz-12 GHz) having cylindrical, conical and stair shaped dielectrics. The study is carried out using Computer Simulation Technology (CST) Microwave Studio. The simulated DRA's have wide impedance bandwidth; around 37.58% for cylindrical, 48.61% and 55.55% for the conical and the two SSS designs. The two SSS gives the best impedance bandwidth in free space and is used for the simulations on the healthy and malignant breast model in which the return loss is used to analyze its effect.
27th Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2019 -- Sivas Cumhuriyet Univ, Sivas, TURKEY
Keywords: Early breast cancer detection (EBCD); conical dielectric resonator antenna (DRA); step stair-shaped (SSS); cylindrical DRA; bandwidth